Analisis Produktivitas Produksi Keripik Tempe “Sagu” UD. Arya Putra Surabaya Dengan Menggunakan Metode Objective Matrix (OMAX) - Damariandini, Natasya; Harsojuwono, Bambang Admadi; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 3 (2023): Seeptember, 2023)
“Sago” tempeh chips are a soy-based snack. UD. Arya Putra is one of the “sago” tempeh chips producers in East Java. Productivity measurement is carried out as an effort to evaluate existing productivity within the company s that the company can develop optimal production targets. The Objective Matrix (OMAX) method is used to measure the productivity of  UD. Arya Putra's “sago” tempeh chip production using 3 criteria, namely efficiency, effectiveness and inferential. The highest peak of productivity value of “sago” tempeh chips production by UD. Arya Putra was found in August 2022 with a productivity index value of 382.9 %  and the lowest peak was found in July 2022 with a productivity index value of 197.6 %. Analysis of the productivity ratio of  “sago ” tempeh chips from UD. Arya Putra who got the highest productivity value, namely ratio 2 (The total value of the product produced is compared to the total cost of LPG usage) worth 384.1 while the lowest productivity value was ratio 6 (Total hours of machine maintenance compared to the total hours of normal machine operation) worth 231 ,7. Proposals for improving productivity that can be given are reducing employee working hours to 191 hours, saving LPG gas to Rp. 5,020,062, optimizing the use of raw materials to Rp. 19,824,116 increasing the value of the products produced to Rp. 150,659,134 and optimizing machine working hours to 74 hours per month . Keywords :  productivity, production, objective matrix (OMAX ) .  Keripik tempe “sagu” merupakan makanan ringan berbahan dasar kedelai. UD. Arya Putra merupakan salah satu produsen keripik tempe ”sagu” di Jawa Timur. Pengukuran produktivitas dilakukan sebagai salah satu upaya untuk mengevaluasi produktivitas yang ada dalam perusahaan sehingga, perusahaan dapat menyusun capaian target produksi yang optimal. Metode Objective Matrix (OMAX) digunakan untuk mengukur produktivitas produksi keripik tempe “sagu” UD.Arya Putra dengan menggunakan 3 kriteria, yaitu efisiensi, efektivitas dan inferensial. Puncak tertinggi dari nilai produktivitas produksi keripik tempe ”sagu” UD. Arya Putra terdapat pada bulan Agustus 2022 dengan perolehan nilai indeks produktivitas sebesar 382,9 persen sedangkan, nilai teredah terdapat pada bulan Juli 2022 dengan nilai indeks produktivitas sebesar 168,3 persen. Analisis rasio produktivitas keripik tempe ”sagu” UD. Arya Putra yang mendapatkan nilai produktivitas tertinggi yaitu rasio 2 (Total nilai produk yang dihasilkan dibandingkan dengan total biaya penggunaan LPG) senilai 384,1 sedangkan nilai produktivitas terendah yaitu rasio 6 (Total jam perawatan mesin dibandingkan dengan total jam operasional mesin normal) senilai 231,7.Usulan perbaikan produktivitas yang dapat diberikan yaitu pengurangan jam kerja karyawan menjadi 191 jam, penghematan gas LPG menjadi Rp. 5.020.062, mengoptimalkan penggunaan bahan baku menjadi Rp. 19.824.116, menambah nilai produk yang dihasilkan menjadi Rp. 150.659.134 serta mengoptimalkan jam kerja mesin menjadi 74 jam setiap bulannya. Kata Kunci:  produktivitas, produksi, objective matrix (OMAX)